The enemy of the feet blisters in ultraendurance runners - Scheer, Bernd Volker; Reljic, Dejan; Murray, Andrew; Costa, Ricardo Jose Soures (Journal of the American Podiatric Medical Association, 2014)
Background: Blisters are the most common dermatologic problem in ultraendurance runners. Their incidence, localization, pain scores, and risk factors in field conditions are poorly understood. Methods: We conducted an observational field-based cohort study during the 5-day multistage 2010 and 2011 Al Andalus Ultimate Trail (219 km). Daily postrace data on blister frequency, localization, severity, and preventive measures from 50 ultramarathon runners were collected through the direct interview technique. Results: After 4 days of running (182 km), blisters occurred in 76% of the participants (P <.001 versus stage 1) compared with 34% after day 1, 54% after day 2, and 72% after day 3 (P,.001 versus stage 1). Most of the blisters formed on the toes (65%) (P <.001), followed by blisters on other locations of the foot: the ball of the foot (16%), heel (14%), and sole (5%). Blisters were more painful toward the end of the race, and those on the sole and heel tended to be the most painful, although this did not reach statistical significance. Prophylactic measures studied (type and fabric of socks; application of antiperspirants, talcum powder, or lubricant to feet; and prophylactic taping) did not show any reduction in blister rates. The only predictive marker for reduced blister incidence was previous ultramarathon experience in men (r =-0.44, P <.05). Conclusions: Blisters are extremely common in multistage ultramarathon races. Race experience in male ultramarathon runners is associated with reduced blister rates.
CRIS-Team Scopus Importer:2022-10-11